Consensus statement on current and emerging methods for the diagnosis and evaluation of cerebrovascular disease. Issue 9 (September 2018) - Donahue, Manus J; Achten, Eric; Cogswell, Petrice M; De Leeuw, Frank-Erik; Derdeyn, Colin P; Dijkhuizen, Rick M; Fan, Audrey P; Ghaznawi, Rashid; Heit, Jeremy J; Ikram, M Arfan; Jezzard, Peter; Jordan, Lori C; et al.
Cerebrovascular disease (CVD) remains a leading cause of death and the leading cause of adult disability in most developed countries. This work summarizes state-of-the-art, and possible future, diagnostic and evaluation approaches in multiple stages of CVD, including (i) visualization of sub-clinical disease processes, (ii) acute stroke theranostics, and (iii) characterization of post-stroke recovery mechanisms. Underlying pathophysiology as it relates to large vessel steno-occlusive disease and the impact of this macrovascular disease on tissue-level viability, hemodynamics (cerebral blood flow, cerebral blood volume, and mean transit time), and metabolism (cerebral metabolic rate of oxygen consumption and pH) are also discussed in the context of emerging neuroimaging protocols with sensitivity to these factors. The overall purpose is to highlight advancements in stroke care and diagnostics and to provide a general overview of emerging research topics that have potential for reducing morbidity in multiple areas of CVD.